Executive directors' compensation and monitoring: the influence of gender diversity on Spanish boards - Baixauli-Soler, J. Samuel; Lucas-Perez, M. Encarnacion; Martin-Ugedo, Juan Francisco; Minguez-Vera, Antonio; Sanchez-Marin, Gregorio (Journal of Business Economics and Management, 2016)
This study presents evidence of the influence of gender diversity on the pay system and the monitoring of executives in Spain. In this country/context, characterized by a few male dominant shareholders acting simultaneously as executives, there is an ongoing discussion regarding the enactment of laws to promote gender equality on the boards of directors of large listed companies. This paper presents several contributions. On the one hand, the scarce previous evidence on this topic is focused on US firms. On the other hand, this study includes the role of ownership structure as a factor that indirectly moderates the relationships between gender diversity on board and monitoring effectiveness in terms of executive directors’ compensation. Furthermore, this paper makes an important effort to control endogeneity. The sample examined includes 120 companies listed on the Spanish stock market during the period 2004–2011. The results show a positive and highly significant effect of the presence of women independent directors on the proportion of variable pay in the compensation of executive directors. Our findings also point out the negative moderating effect of ownership concentration: the more concentrated is ownership in the hands of internal majority shareholder, the less is the link between board diversity and pay-for-performance systems.